Development of microsatellite markers for the resin‐yielding, non‐timber forest product species Boswellia serrata (Burseraceae). (19th September 2018) - Maradani, Bhavani Shankar; Gudasalamani, Ravikanth; Setty, Siddappa; Chandrasekaran, Rajasekaran
Abstract : Premise of the Study: Boswellia serrata (Burseraceae) is an economically important aromatic, gum‐resin–yielding, non‐timber forest tree species. Microsatellite markers were developed for B. serrata for the first time to study genetic diversity and population structure. Methods and Results: A magnetic bead enrichment method was used to develop 16 microsatellite markers, of which 11 were polymorphic. The number of alleles per locus in the 60 individuals studied ranged from three to 10, and the levels of observed and expected heterozygosity ranged from 0.50 to 0.90 and 0.666 to 0.861, respectively. The primers successfully amplified in the congeneric species B. ovalifoliolata . Conclusions: These microsatellite markers can be used to study the genetic variation and population structure of B. serrata and to provide crucial information on population and ecological issues for management and conservation of the species.